KORELASI MASA KERJA, JAM KERJA TERHADAP KADAR t,t- MOCONIC ACID URIN PEKERJA TERPAPAR BENZENA DI PERTAMBANGAN MINYAK TRADISIONAL BOJONEGORO - Saadatuddaroini Saadatuddaroini; Soedjajadi Keman (The Indonesian Journal of Occupational Safety and Health, 2019)
Benzene is a natural compound contained in petroleum. Exploitation of petroleum can be done traditionally and modern. Exposure in traditional oil mining contained benzene compound can cause high levels of urine t,tmuconic acid in workers. The highest urine t,t-muconic acid levels can be affected by several factors including work period and work duration. The aim of this study was to analyzed the correlation between work period and work duration to urine t,t-muconic acid levels in traditional oil mining workers. This was an observational study with cross sectional approach. Eleven (11) sample was drawn from twelve (12) population of traditional oil mining workers. The variables studied were urine t,t-muconic acid levels, work period and work duration. Methods of data analysis to known the correlation between variabels used spearmen correlation test with α=0.05. The result showed that benzene level in ambien air measured at 4 points were exceeded the threshold limit while, 72.3% of workers had t,t-muconic acid levels within urine highest the BEIs levels. Work period and work duration were significally correlated to urine t,t- muconic acid levels (all variables, p<0.05). It can be concluded that the longer the work period and work duration were the highest the t,t-muconic acid levels of urine would be.Keywords: traditional oil mining, urine t,t-muconic acid levels, work duration, work time